2014
DOI: 10.1371/journal.pone.0108176
|View full text |Cite
|
Sign up to set email alerts
|

Part-Based and Configural Processing of Owner's Face in Dogs

Abstract: Dogs exhibit characteristic looking patterns when looking at human faces but little is known about what the underlying cognitive mechanisms are and how much these are influenced by individual experience. In Experiment 1, seven dogs were trained in a simultaneous discrimination procedure to assess whether they could discriminate a) the owner's face parts (eyes, nose or mouth) presented in isolation and b) whole faces where the same parts were covered. Dogs discriminated all the three parts of the owner's face p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 76 publications
(100 reference statements)
4
30
0
Order By: Relevance
“…The latter ability was tested in our lab using the touch-screen technology. We found that dogs can discriminate human faces by using the internal facial features (eyes, nose, mouth and their configuration) only (Pitteri et al, 2014). Other recent data from our lab suggest that dogs share with human infants a pattern of visual preferences for features consistent with the human eye (local contrast polarity) that may represent a foundational perceptual tool for life in human society.…”
supporting
confidence: 48%
“…The latter ability was tested in our lab using the touch-screen technology. We found that dogs can discriminate human faces by using the internal facial features (eyes, nose, mouth and their configuration) only (Pitteri et al, 2014). Other recent data from our lab suggest that dogs share with human infants a pattern of visual preferences for features consistent with the human eye (local contrast polarity) that may represent a foundational perceptual tool for life in human society.…”
supporting
confidence: 48%
“…It is unlikely that dogs simply are working hard to attend to all the facial elements to look for information, because, if this was the case, the areas of the face attended to should reflect the information available from these regions in any given state. Instead, the configural processing of familiar faces in dogs (Pitteri et al 2014) is here extended to facial expressions. Configural processing (sensu Bruce and Young 2012) is early and well developed in humans (de Heering et al 2007), and found in varied taxa, including chimpanzees (Parr et al 2008), sheep (Kendrick et al 1996), pandas (Li et al 2017), and even bees (Dyer 2005).…”
Section: Dog Perception Of Facial Expressionsmentioning
confidence: 99%
“…They are able to discriminate familiar human faces using the global visual information both of the faces and the head (Huber, Racca, Scaf, Virányi, & Range, 2013), scanning all the facial features systematically (e.g. eyes, nose and mouth; Somppi et al, 2016) and relying on configural elaboration (Pitteri, Mongillo, Carnier, Marinelli, & Huber, 2014). Moreover, dogs, as well as humans, focus their attention mainly in the eye region, showing faces identification impairments when it is masked (Pitteri et al, 2014;Somppi et al, 2016).…”
mentioning
confidence: 99%
“…eyes, nose and mouth; Somppi et al, 2016) and relying on configural elaboration (Pitteri, Mongillo, Carnier, Marinelli, & Huber, 2014). Moreover, dogs, as well as humans, focus their attention mainly in the eye region, showing faces identification impairments when it is masked (Pitteri et al, 2014;Somppi et al, 2016). Interestingly, their gazing pattern of faces informative regions varies according to the emotion expressed.…”
mentioning
confidence: 99%